2016
DOI: 10.1080/09674845.2016.1220707
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 polymorphisms and steroid treatment in children with idiopathic nephrotic syndrome

Abstract: Our results suggested that C1236T polymorphism in ABCB1 gene was associated with steroid resistance. A higher proportion of SR children had C1236T TT genotype and T allele, these patients may require other therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…The subjects in 4 studies were Asian [ 16 , 17 , 34 , 35 ] and those from the other 5 were Caucasian. [ 14 , 15 , 31 33 ] Seven studies reported genotype frequencies between patients with INS and healthy controls, [ 14 16 , 31 , 32 , 34 , 35 ] and 7 studies showed the genotype data of SS and SR groups. [ 14 17 , 32 , 33 , 35 ] Haplotype frequencies of both case and control cohorts were described in part in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects in 4 studies were Asian [ 16 , 17 , 34 , 35 ] and those from the other 5 were Caucasian. [ 14 , 15 , 31 33 ] Seven studies reported genotype frequencies between patients with INS and healthy controls, [ 14 16 , 31 , 32 , 34 , 35 ] and 7 studies showed the genotype data of SS and SR groups. [ 14 17 , 32 , 33 , 35 ] Haplotype frequencies of both case and control cohorts were described in part in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 , 15 , 31 33 ] Seven studies reported genotype frequencies between patients with INS and healthy controls, [ 14 16 , 31 , 32 , 34 , 35 ] and 7 studies showed the genotype data of SS and SR groups. [ 14 17 , 32 , 33 , 35 ] Haplotype frequencies of both case and control cohorts were described in part in 4 studies. [ 14 , 15 , 32 , 35 ] SS and SR groups were also compared in 4 studies (details provided in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to evaluate the association of P-glycoprotein polymorphisms with the responsiveness to glucocorticoids in patients with nephrotic syndrome. The results of these studies on the significance of the genetic polymorphisms are contradictory [ 71 , 82 84 , 86 , 104 , 120 , 121 ]. A recent meta-analysis concluded that there is evidence of an association between rs1128503 and increased risk of steroid resistance in children with nephrotic syndrome [ 122 ].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Aside from the obvious connection between glucocorticoid receptor (GR) function and corticosteroid response, the products of CYP3A4, CYP3A5 , and ABCB1 are required for metabolism of calcineurin inhibitors like tacrolimus, providing biologic relevance to these variant associations. However, while associations have been identified between variants in GR and ABCB1 and steroid response in patients with NS, none of these genes have been found to be associated with increased incidence of SSNS (Table 4) (95103). Additional associations between biologically relevant molecules and steroid response or relapse rates in NS patients including variants in genes encoding important signaling molecules such as Tumor necrosis factor alpha ( TNF α), Angiotensin-converting enzyme ( ACE ), Interleukin 4 ( IL4 ), and Interleukin 12 ( IL12B promoter) have been reported (Table 4) (104108).…”
Section: Evidence That Ssns Has Strong Genetic Componentmentioning
confidence: 99%